Signal-amplifying nanoparticle/hydrogel hybrid microarray biosensor for metal-enhanced fluorescence detection of organophosphorus compounds. (16th March 2018) - Kim, Minsu; Kwon, Ji Eon; Lee, Kangwon; Koh, Won-Gun
Abstract: In this study, we developed an enzyme-based miniaturized fluorescence biosensor to detect paraoxon, one of the most well-known neurotoxic organophosphorus compounds. The biosensor was fabricated with poly(ethylene glycol) (PEG) hydrogel microarrays that entrapped acetylcholinesterase (AChE) and quantum dots (QDs) as fluorescence reporters. Metal-enhanced fluorescence (MEF) was utilized to amplify the fluorescence signal, which was achieved by decorating QDs on the surface of silica-coated silver nanoparticles (Ag@Silica). The MEF effects of Ag@Silica were optimized by tuning the thickness of the silica shells, and under the optimized conditions, the fluorescence intensity was shown to be increased 5 fold, compared with the system without MEF. PEG hydrogel microarray entrapping QD-decorated Ag@Silica and AChE was prepared via photopatterning process. The entrapped AChE hydrolyzed paraoxon to produce p-nitrophenol within the hydrogel microstructure, which subsequently quenched the fluorescence of the QDs on the surface of Ag@Silica. The MEF-assisted fluorescence detection resulted in a significant enhancement of paraoxon detection. The detection limit was approximately 1.0 × 10 −10 M and 2.0 × 10 −7 M for sensing with and without MEF, respectively. The successful integration of a hydrogel microarray system with a microfluidic system was demonstrated to be a potential application for the MEF-based micro-total-analysis-system.